Peningkatan Ekonomi Masyarakat Penyulingan Minyak Cengkeh Di Desa Batu Kecamatan Pitumpanua Kabupaten Wajo - Thamrin Abduh; Jamil Gunawi; Arman Setiawan (Jurnal TUNAS, 2021)
Batu Village is a planned location for the PPPUD program which has two main activities carried out by the community, namely; some of the community is a farmer group (partner I) and there are also some people who choose to do the clove oil refining process (partner 2). In particular, the farmer groups (partner I) generally sell agricultural produce from plantations such as cloves and cocoa, while clove leaves are distilled. But the process of processing clove leaves, starting from the handling of raw materials, drying, and drying, is still done very simply or traditionally by spreading clove leaves on mats or on the side of the road in an open state. This results in many clove leaves that are of poor quality processed. Not hygienic (dusty), ultimately clove oil is less attractive to consumers, so that it is detrimental to farmer groups who carry out the process of refining clove oil. The amount of clove oil produced by farmer groups and SMEs (partners) is currently an average of 100 - 150 liters per week with very low quality durability. The total population of Batu village is 4701 people consisting of 2298 men and 2403 women with a total of 820 people in 6 hamlets, namely Temboe, Sampano, Batu Lotong, Tarere, Metali and Ponnori hamlets with an education level of almost 80%. elementary school or equivalent with an area of 535 square km.